2010
DOI: 10.1371/journal.pone.0012913
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Human AKT1 with an Allosteric Inhibitor Reveals a New Mode of Kinase Inhibition

Abstract: AKT1 (NP_005154.2) is a member of the serine/threonine AGC protein kinase family involved in cellular metabolism, growth, proliferation and survival. The three human AKT isozymes are highly homologous multi-domain proteins with both overlapping and distinct cellular functions. Dysregulation of the AKT pathway has been identified in multiple human cancers. Several clinical trials are in progress to test the efficacy of AKT pathway inhibitors in treating cancer. Recently, a series of AKT isozyme-selective allost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
292
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 283 publications
(317 citation statements)
references
References 30 publications
10
292
1
4
Order By: Relevance
“…Recent structural studies indicate that inhibitory interdomain interactions play a crucial role in regulating AKT activation (15,17). Using a mutational screen, we show here that activation of AKT can result from mutations in residues involved in PH-KD contacts.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Recent structural studies indicate that inhibitory interdomain interactions play a crucial role in regulating AKT activation (15,17). Using a mutational screen, we show here that activation of AKT can result from mutations in residues involved in PH-KD contacts.…”
Section: Discussionmentioning
confidence: 85%
“…Several ATP-competitive and allosteric smallmolecule inhibitors of AKT are in development and/or clinical trials (36,37). Previous studies have shown that allosteric AKT inhibitors require an intact PH-KD interface for their activity (17,(38)(39)(40). Given that some AKT1 somatic mutants have impaired PH-KD contacts, we predicted that allosteric inhibitors are likely to be less efficacious in inhibiting their activity.…”
Section: Disruption Of Akt2 and Akt3 Ph-kd Interactions Leads To Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, this complex has been considered during the pharmacophore generation process as model for other pharmacophore realization and to find a promising molecule as lead compound that could become a new potential drug [4].…”
Section: Search In Pdb Database Of a Model Structure For Akt1mentioning
confidence: 99%
“…A study using transgenic mice showed that overexpression of Akt3-v1 was cardioprotective in a short-term, but eventually resulted in cardiohypertrophy (24). The recently published crystallization data of the Akt2 kinase domain and the protein structure of Akt1 bound to an allosteric inhibitor (Akt1/2 inhibitor VIII) will further facilitate our understanding of the isoform-specific Akt function (25,26).…”
Section: Gene and Amino Acid Sequences Of The Akt Isoformsmentioning
confidence: 99%